STRATEGI KOMUNIKASI PEMASARAN DALAM MEMPENGARUHI KEPUTUSAN KONSUMEN AYAM GEPUK PAK GEMBUS CABANG SRENGSENG SAWAH - Dadang Syaputra; Nova Darmanto; Muhamad Ridwan (Jurnal Ilmiah Publipreneur, 2022)
ABSTRACTThis study aims to determine how much influence the marketing strategy has on consumer decisions in choosing the Ayam Gepuk Pak Gembus restaurant in Srengseng Sawah. The population in this study is all people who live in South Jakarta with the sample in this study is 110 respondents and the technique used is random sampling technique (random sampling). Data collection techniques used in this study were interviews with the help of questionnaires and documentation. The answers given by the respondents were analyzed quantitatively using the SPSS program. The quality of the research data was tested with validity and reliability tests and the classical assumption test was carried out, namely normality, multicollinearity and heteroscedasticity tests before linear regression analysis was carried out. From the results of the analysis, all indicators in this study were declared valid and reliable. From the classical assumption test, it is declared feasible and the test results state that all variables have a positive and significant influence either simultaneously or partially. The writer's suggestion is that the Ayam Gepuk Pak Gembus restaurant in Srengseng Sawah Branch must maintain and even improve its marketing strategy so that it will have an impact on consumer decisions. Ayam Gepuk Pak Gembus Restaurant must fix problems related to variables that can affect purchasing decisions such as location, this is very important because it considers current consumer behavior which also prioritizes a comfortable, safe and conducive location to support service from the product quality indicators we provide. provide.Â Keywords: Location, price, product, promotion and purchase decision